Gestão da qualidade e resistência à mudança estratégias para a evolução empresarial descomplicada - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2025)
Resistance to change is one of the main challenges in implementing and evolving quality management in organizations, directly affecting operational efficiency and stakeholder satisfaction. Classical and contemporary authors emphasize that such resistance can delay the adoption of qualitative practices, making it harder for companies to adapt to a competitive environment. Given this scenario, this study sought to identify the factors that intensify this barrier in order to propose simpler and more effective strategies to overcome it. With a qualitative, descriptive and exploratory approach, based on a bibliographic review, this research provided already consolidated practical guidelines for managers and consultants, facilitating the adoption of quality management systems and promoting the sustainable evolution of organizations.
Keywords: Gestão de Qualidade; Estratégias Organizacionais; CNPQ::CIENCIAS SOCIAIS APLICADAS::ADMINISTRAÇÃO